Analisis Masyarakat Konsumsi: Komodifikasi Jomblo Melalui Speed Dating - Intihaul Khiyaroh (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The definition of single is interpreted as a title that some people consider acurse for those who do not have a partner. In this era of digital development, global capitalism is using it to take advantage of the singles title by creating dating applications. The consumption style, which is guided by advertising in global capitalism, has in fact created a consumer society that consumes, which seems to be the